3(x+2)=5(2x+1)

Simple and best practice solution for 3(x+2)=5(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=5(2x+1) equation:


Simplifying
3(x + 2) = 5(2x + 1)

Reorder the terms:
3(2 + x) = 5(2x + 1)
(2 * 3 + x * 3) = 5(2x + 1)
(6 + 3x) = 5(2x + 1)

Reorder the terms:
6 + 3x = 5(1 + 2x)
6 + 3x = (1 * 5 + 2x * 5)
6 + 3x = (5 + 10x)

Solving
6 + 3x = 5 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
6 + 3x + -10x = 5 + 10x + -10x

Combine like terms: 3x + -10x = -7x
6 + -7x = 5 + 10x + -10x

Combine like terms: 10x + -10x = 0
6 + -7x = 5 + 0
6 + -7x = 5

Add '-6' to each side of the equation.
6 + -6 + -7x = 5 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = 5 + -6
-7x = 5 + -6

Combine like terms: 5 + -6 = -1
-7x = -1

Divide each side by '-7'.
x = 0.1428571429

Simplifying
x = 0.1428571429

See similar equations:

| x^2+28x-480=0 | | x^3+3x^2-4x-12= | | 2.7=1.3-2d | | 3(4x-1)=4-2(5-3x) | | 3x^2+13x-16=0 | | 4(3x+2)=5(2x+1) | | -4(14-x)+14(2)= | | 9x^3+x^2-8x-9=0 | | 3y+4y-14=0 | | 64+3x=5x+43 | | -15+3x=0 | | -7x=-4x^2+15 | | 3(2x+1)=5x-3 | | 3w+1=25 | | 5y-3+y+23=7y+20-5y | | 37-14=37-x | | 4x+5(7x+-3)=9(x+-5) | | X^2+22x+57=0 | | X^3-5x^2+9x=0 | | (25x/100)*20= | | (-8)+3x=5x+43 | | 16+2b=b^2-4b | | 3b=5b+24 | | 12-h=3-h | | 37x-14=(34x-4)7 | | 7x-4x+2x+5=2x+14 | | 32-0.35y=0.75y+5 | | 6x+8=9.8 | | (6x+8)+(9x+25)=180 | | -68=4-4n | | 2x^4+x^3-3x+4=0 | | 4x^2-5x+4=0 |

Equations solver categories